Tata Kelola Rekam Medis Berbasis Elektronik Pada Kunjungan Harian Pasien Rawat Jalan Menggunakan Metode RAD - Pradysta, Linggar Adjie; Syahidin, Yuda; Sari, Irda (Program Studi Teknik Informatika Universitas Pamulang, 2023)
Problems faced in the governance of electronic-based medical records in outpatient daily visits include the lack of governance standards, inconsistencies in data collection, and low interoperability between existing systems. These problems can lead to errors in diagnosis, less efficient treatment, and increased patient safety risks. In order to solve these problems, the RAD (Rapid Application Development) method was proposed as a solution. This method involves a needs analysis phase conducted by listening to stakeholders, identifying existing problems, and designing a suitable solution. The use of the RAD method can provide significant results. After the implementation of the RAD method, the results showed significant improvement. Clear and measurable governance standards have been implemented to ensure consistency and accuracy in data collection. In addition, faster system development is also possible through the implementation of the RAD method, thus overcoming the technical challenges associated with electronic medical records. Overall, the results of applying the RAD method in the governance of electronic-based medical records on daily outpatient visits have successfully addressed the existing problems. This method can be widely applied in clinical practice to improve efficiency, quality of care and patient safety.